IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS ETNOPEDAGOGI ULELEAN PARE UNTUK MENCEGAH PERUNDUNGAN DI UPT SDN 6 MENGKENDEK - Delvi, Marsanda; Sangkung Panggalo, Iindarda; Rante, Marchelina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Character education is the foundational stage for young children that needs to be carefully prepared, especially at the elementary school level. Ulelean Pare is a folk tale passed down orally from generation to generation. This study aims to identify the ethnopedagogical values in Ulelean Pare that are relevant to students' character education, describe the understanding and internalization process of Ulelean Pare's values among third-grade students at UPT SDN 6 Mengkendek, and analyze the impact of implementing these values on students' social behavior in preventing bullying. This research uses a descriptive qualitative method. Data collection techniques were carried out through observation, interviews, and documentation. The results show changes in students' behavior, marked by increased cooperation, empathy, courage to speak, and a decrease in mocking and excluding friends. The benefit of this research is as a source of moral education.